Development of a PjBL-Based E-Booklet on Temperature and Heat Integrated with the Local Wisdom of Magelang Pottery to Equip Students with Creative Thinking Skills - Ully Ismayati; Sudarmin Sudarmin; Woro Sumarni; Sunyoto Eko Nugroho (International Journal of Active Learning, 2026)
Problem: the integration of local wisdom in junior secondary science learning remains limited, contributing to low students’ creative thinking skills. Furthermore, the use of digital teaching materials that support project-based learning is not yet optimal, resulting in less contextual and engaging learning. Objective: this study aimed to develop and examine the feasibility and effectiveness of a Project-Based Learning (PjBL)-based e-booklet on temperature and heat integrated with the local wisdom of Magelang pottery. Method: this research employed a Research and Development (R&D) approach using the ADDIE model and involved an experimental and a control class. The evaluation focused on feasibility (validity, readability, and practicality) and efeftiviness (product and process performance, as well as learning outcomes). Results: the developed e-booklet was found to be valid, practical, and received positive responses from students. Conclusion: the e-booklet was sufficiently effective in enhanving student engagement and creative thinking skills, making it a feasible contextual teaching material for junior secondary science learning.